Fucofuroeckol-A from Eisenia bicyclis Inhibits Inflammation in Lipopolysaccharide-Induced Mouse Macrophages via Downregulation of the MAPK/NF-κB Signaling Pathway - Sang-Hoon Lee; Sung-Hwan Eom; Na-Young Yoon; Moon-Moo Kim; Yong-Xin Li; Sang Keun Ha; Se-Kwon Kim (Journal of Chemistry)
Fucofuroeckol-A (FF) isolated from an edible perennial brown seaweed Eisenia bicyclis was shown to be potent anti-inflammatory agents. FF suppressed the production of nitric oxide (NO) and prostaglandin E2 (PGE2) and the expression of inducible nitric oxide synthase and cyclooxygenase-2 dose dependently in lipopolysaccharide- (LPS-) induced RAW 264.7 mouse macrophages. An enzyme-linked immunosorbent assay and cytometric bead array assay demonstrated that FF significantly reduced the production of proinflammatory cytokines, such as interleukin-6 and tumor necrosis factor-α, and that of the monocyte chemoattractant protein-1. Moreover, FF reduced the activation of nuclear factor κB (NF-κB) and mitogen-activated protein kinases (MAPKs). These results strongly suggest that the inhibitory effects of fucofuroeckol-A from E. bicyclis on LPS-induced NO and PGE2 production might be due to the suppression of the NF-κB and MAPK signaling pathway.